Evaluation of guidelines for injured children at high risk for venous thromboembolism: A prospective observational study. Issue 5 (May 2017) - Landisch, Rachel M.; Hanson, Sheila J.; Cassidy, Laura D.; Braun, Kristin; Punzalan, Rowena C.; Gourlay, David M.
Abstract : BACKGROUND: Pharmacologic prophylaxis for venous thromboembolism (VTE) is a widely accepted practice in adult trauma patients to prevent associated morbidity and mortality. However, VTE prophylaxis has not been standardized in injured pediatric patients. Our institution identified factors potentially associated with a high risk of VTE in critically injured children that led to prospective implementation of VTE prophylaxis guidelines. We hypothesize that the guidelines are accurate in predicting children at risk for VTE. METHODS: Data were prospectively collected on injured children from August 2010 to August 2015. Pharmacologic prophylaxis was indicated for patients identified by the guidelines as high risk for VTE. Prophylaxis was deferred and a screening ultrasound was performed if the high-risk VTE patients were also at high risk for bleeding. To assess the accuracy of predicting confirmed cases of VTE, stepwise logistic regression analysis was used to measure the association of individual risk factors with VTE controlling for age (≥13 years). A receiver operating characteristic curve measured the accuracy of the final model to predict a VTE. RESULTS: Of 4, 061 trauma patients, 588 were admitted to the ICU, with the guidelines identifying 199 as high risk for VTE. VTE occurred in 3.9% (23/588) of the ICU population and 10% (20/199) of the high risk group. The median age of VTE patients in the ICU was 9.7 years. Statistically significant predictors ( p < 0.05) of VTE in the multivariate model included presence of a central venous catheter (OR = 5.2), inotropes (OR = 7.7), immobilization (OR = 5.5), and a Glasgow Coma Scale of <9 (OR = 1.3). The area under receiver operating characteristic curve of this model was 0.92, demonstrating its excellent predictive ability. CONCLUSION: Specific clinical factors in critically injured children are associated with a high risk for VTE. Incorporating these risk factors in VTE prophylaxis guidelines facilitates more accurate risk stratification and may allow for improved VTE prevention in pediatric trauma. LEVEL OF EVIDENCE: Prognostic study, level II.